Random allocation or allocation at random? Patients’ perspectives of participation in a randomised controlled trial - Featherstone, Katie (British Medical Journal, 1998)
Objectives To explore trial participants’ understandings of randomisation. Design In this exploratory study, which used qualitative research methods, in-depth, semistructured interviews were carried out with 20 participants from the CLasP randomised controlled trial. Interviews were recorded on audio tape and fully transcribed. Data were analysed by comparing transcripts and describing emergent themes, using a grounded theory approach. Setting The CLasP study comprises three linked multicentre, pragmatic randomised controlled trials evaluating the effectiveness and cost effectiveness of laser therapy, standard surgery, and conservative management for men with lower urinary tract symptoms or urinary retention, or both, related to benign prostatic disease. Subjects 20 participants in the CLasP study were interviewed. Sampling was purposeful: men were included from each of the treatment arms, the two major centres, and at different points in the trial. Interventions and outcome measures Interviews used a checklist of topics to encourage participants to describe their experiences. Narratives concerning randomisation were compared to identify common themes, retaining the context of the discussion to allow detailed interpretation. Results Most participants recalled and described aspects of randomisation, such as the involvement of chance, comparison, and concealed allocation. Many found the concept of randomisation difficult, however, and developed alternative lay explanations to make sense of their experiences. Inaccurate patient information and lay interpretations of common trial terms caused confusion. Conclusions The provision of clear and accurate patient information is important, but this alone will not ensure consistent interpretation of concepts such as randomisation. Patients may need to discuss the purposes of randomisation in order to understand them fully enough to give truly informed consent.